The T-box transcription factor Eomesodermin acts upstream of Mesp1 to specify cardiac mesoderm during mouse gastrulation. - Costello, I; Pimeisl, I; Dräger, S; Bikoff, E; Robertson, E; Arnold, S (2011)
Instructive programmes guiding cell-fate decisions in the developing mouse embryo are controlled by a few so-termed master regulators. Genetic studies demonstrate that the T-box transcription factor Eomesodermin (Eomes) is essential for epithelial-to-mesenchymal transition, mesoderm migration and specification of definitive endoderm during gastrulation. Here we report that Eomes expression within the primitive streak marks the earliest cardiac mesoderm and promotes formation of cardiovascular progenitors by directly activating the bHLH (basic-helix-loop-helix) transcription factor gene Mesp1 upstream of the core cardiac transcriptional machinery. In marked contrast to Eomes/Nodal signalling interactions that cooperatively regulate anterior-posterior axis patterning and allocation of the definitive endoderm cell lineage, formation of cardiac progenitors requires only low levels of Nodal activity accomplished through a Foxh1/Smad4-independent mechanism. Collectively, our experiments demonstrate that Eomes governs discrete context-dependent transcriptional programmes that sequentially specify cardiac and definitive endoderm progenitors during gastrulation.